A Tale of 2 Pneumos: The Impact of Human Immunodeficiency Virus Exposure or Infection Status on Pediatric Nasopharyngeal Carriage of Streptococcus pneumoniae and Pneumocystis jiroveci: A Nested Case Control Analysis From the Pneumonia Etiology Research In Child Health Study. (15th February 2020) - Camelo, Ingrid Y; Mwananyanda, Lawrence M; Thea, Donald M; Seidenberg, Philip; Gill, Christopher J; Weinstein, John R
Abstract: Background: The majority of pediatric human immunodeficiency virus (HIV) cases in Africa reflect maternal-to-child transmission. HIV exposed but uninfected (HEU) children have increased rates of morbidity and mortality when compared to HIV unexposed and uninfected (HUU) children. The mechanisms behind these unexpected trends are only partially understood but could be explained by the differences in the immune response to infections triggered by an altered immune system state. Methods: Using quantitative reverse transcription polymerase chain reaction, we compared the nasopharyngeal carriage prevalence and density of Streptococcus pneumoniae (SP) and Pneumocystis jirovecii (PJ) between children living with HIV and HEU or HUU cases (pneumonia) and controls (without pneumonia). Results: The cohort included 1154 children (555 cases and 599 matched controls). The SP carriage prevalence rates were similar between cases and controls. Among SP carriers with pneumonia, carriage density was increased among children living with HIV, versus HEU or HUU children (15.8, 4.7, and 3.6 × 10 5 copies/mL, respectively). The rate of PJ carriage was significantly higher among children living with HIV than among HEU and HUU children (31%, 15%, and 10%, respectively; P  < .05), as was carriage density (63.9, 20.9, and 4.8 × 10 3 copies/mL, respectively; P  < .05). Conclusions: Carriage prevalences and densities for SP and PJ show different kinetics in terms of their relationship with HIV exposure and clinical status, particularly for Pneumocystis jirovecii . This supports the theory that the increased morbidity and mortality observed among HEU children may reflect deficits not just in humoral immunity but in cell-mediated immunity as well. Abstract : In Zambian children living with human immunodeficiency virus (HIV), exposed but living without HIV, and unexposed and living without HIV, the latter experience impaired cell-mediated immunity with Pneumocystis jirovecii nasopharyngeal carriage prevalence and carriage density, but not with Streptococcus pneumoniae.